Determination of ligand position in aspartic proteases by correlating tanimoto coefficient and binding affinity with root mean square deviation - Sandra Megantara & , Maria Immaculata Iwo, Jutti Levita, Slamet Ibrahim (Journal of Applied Pharmaceutical Science, 2016)
The objective of this study was to develop and validate of Structure-Based Virtual Screening (SBVS) protocol which was used to select the best pose of inhibitor-aspartic protease complex interaction in the active sites of HIV-1 protease, plasmepsin I, II, and IV. Retrospective validation was performed on enhanced dataset of ligands and decoys (DUD-E) for HIV-1 protease. The crystal structures 1XL2, 3QS1, 1SME, and 1LS5 were obtained from Protein Data Bank. The protocol was then challenged to re-dock the ligands to its origin places in the active sites by correlating Tanimoto coefficient (Tc) and binding affinity (Ei) with Root Mean Square Deviation (RMSD). Enrichment factor at 1% false positives (EF1%) values for Tc and Ei were 18.26 and 9.03, respectively, while the Area Under Curve (AUC) values for Tc and Ei were 76.84 and 60.95. The SBVS protocol was valid and showed better virtual screening qualities in ligand identification for HIV-1 protease compared to the original protocol accompanying the release of DUD-E and showed its ability to reproduce the co-crystal pose in the HIV-1 protease, plasmepsin I, II, and IV to its origin places in the active sites.
Keywords: HIV-1 protease, inhibitor-aspartic protease, plasmepsins, structure-based virtual screening.